Transcroporal Artificial Urinary Sphincter Placement With Closure of Corporal Bodies—A Long-Term Analysis of Functional Outcomes - Maurer, Valentin; Dahlem, Roland; Howaldt, Marian; Riechardt, Silke; Fisch, Margit; Ludwig, Tim A.; Engel, Oliver (Frontiers in Surgery, 2022)
Objectives An artificial urinary sphincter (AUS) is the gold standard for postoperative stress urinary incontinence (SUI). The transcorporal AUS (TC) placement constitutes the main salvage option in high-risk patients suffering from SUI with fragile urethras. The literature analyzing long-term outcomes with respect to explantation rates, continence, and erectile function is scarce. Methods and Patients Retrospective data collection was performed in 2011. TC was applied according to a standardized protocol. TC was implanted after bulbar urethroplasty or double-cuff (DC) explantation. After TC placement, the tunica albuginea was closed in order to minimize the risk of postoperative bleedings and erectile dysfunction. Activation was performed 6 weeks postoperatively. Further follow-up (FU) was scheduled 6/24 months postoperatively and every 2 years thereafter. Primary/secondary endpoints were explantation/objective, subjective, and social continence rates. Objective or social continence was defined as the use of 0 pads/day or <2 pads/day, respectively. Thereupon, postoperative bleedings and erectile function were analyzed. Results A total of 39 high-risk patients were available for analysis. The median age was 72 years. In total, 84.6%, 10.3%, and 2.6% had a history of radical prostatectomy, TURP, and radical cystectomy, respectively. In total, 61.5% had a history of radiation therapy of the prostate, 41% had a history of urethral surgery, and 95% had a history of double cuff explantation. The median FU was 27 months. Objective, subjective, and social continence were 54.5%, 69.7%, and 78.8%, respectively. The median pad usage was 1 pad/day [1–2.5]. Only one patient suffered from a postoperative hematoma. In total, 15.4% of the patients were able to have an erection preoperatively, compared to 7.7% after TC placement. The estimated mean explantation-free survival of the TC was 83 months in the Kaplan–Meier analysis. Conclusions TC AUS implantation constitutes a viable salvage approach in high-risk SUI patients with a mean device survival of almost 7 years and high social continence rates of almost 80%. An intraoperative closure of the tunica albuginea after TC placement allows for very low rates of postoperative hematoma and supports postoperative erectile rigidity.